Management of Sepsis in the First 24 Hours: Bundles of Care and Individualized Approach - Coloretti, Irene; Tosi, Martina; Biagioni, Emanuela; Busani, Stefano; Girardis, Massimo (Seminars in Respiratory and Critical Care Medicine, 2024)
Early diagnosis and prompt management are essential to enhance the outcomes of patients with sepsis and septic shock. Over the past two decades, evidence-based guidelines have guided appropriate treatment and recommended the implementation of a bundle strategy to deliver fundamental treatments within the initial hours of care. Shortly after its introduction, the implementation of a bundle strategy has led to a substantial decrease in mortality rates across various health care settings. The primary advantage of these bundles is their universality, making them applicable to all patients with sepsis. However, this same quality also represents their primary disadvantage as it fails to account for the significant heterogeneity within the septic patient population. Recently, the individualization of treatments included in the bundle has been suggested as a potential strategy for further improving the prognosis of patients with sepsis. New strategies for the early identification of microorganisms and their resistance patterns, advanced knowledge of antibiotic kinetics in critically ill patients, more conservative fluid therapy in specific patient populations, and early use of alternative vasopressors to catecholamines, as well as tailored source control based on patient conditions and site of infection, are potential approaches to personalize initial care for specific subgroups of patients. These innovative methodologies have the potential to improve the management of septic shock. However, their implementation in clinical practice should be guided by solid evidence. Therefore, it is imperative that future research evaluate the safety, efficacy, and cost-effectiveness of these strategies.
Keywords: sepsis; antibiotic; bundles; source control; vasopressors; fluid